(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The problem in this study is the lack of understanding in learning to calculate addition because it is seen during the observation that there are students who still experience deficiencies in remembering the material that has been studied, especially in calculating additions under 10. This study aims to find out whether using abacus media can improve the ability to calculate addition in mild mentally retarded students at SLB Bhakti Luhur Baumata-Kupang, The research method used is Classroom Action Research as a research procedure that produces data in the form of numbers and written words. Data collection techniques in this study are observation interviews, assessments, documentation. The results of this study indicate that there is an increase in learning outcomes of mentally retarded students in cycle I of 40% SS subjects, 45% MF, 50% EG, increasing to 93% SS subjects, 90% MF, 95% EG in cycle II. The results of the study showed that at the end of cycle II, there was an increase in children’s learning outcomes of 93%, 90%, 95% with the category of Very Good Development.